2006
DOI: 10.1093/intimm/dxl062
|View full text |Cite
|
Sign up to set email alerts
|

 1-Integrins determine the dendritic morphology which enhances DC-SIGN-mediated particle capture by dendritic cells

Abstract: The morphology of antigen-presenting dendritic cells (DCs) is characterized by the presence of numerous long dendrites. The formation of these processes is shown to require the interaction between the beta1-integrin (CD29) on the surface of the DCs and fibronectin in the extracellular matrix. This interaction occurs at focal contacts formed at the tips of dendrites, which contain high concentrations of the beta1-integrins, actin and the cytoskeletal proteins vinculin, paxillin and talin. Dendrites contain an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
5
16
0
Order By: Relevance
“…Nevertheless, the preferential accumulation of DC-SIGN in the leading edge may optimize contact between the dendritic cell and pathogens and/or antigens in sites of infection that enter the DC. Also, the active edges of the dendritic cell lamellipod are known to 'scan' the local environment for efficient particle acquisition (Swetman Andersen et al, 2006); thus, DC-SIGN appears distributed to the active leading edge where it would enhance the antigen-scanning function of the dendritic cell. Little DC-SIGN was observed in the relatively flat ventral membranes of Raji transfectants or within the lamellar membrane of immature dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the preferential accumulation of DC-SIGN in the leading edge may optimize contact between the dendritic cell and pathogens and/or antigens in sites of infection that enter the DC. Also, the active edges of the dendritic cell lamellipod are known to 'scan' the local environment for efficient particle acquisition (Swetman Andersen et al, 2006); thus, DC-SIGN appears distributed to the active leading edge where it would enhance the antigen-scanning function of the dendritic cell. Little DC-SIGN was observed in the relatively flat ventral membranes of Raji transfectants or within the lamellar membrane of immature dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that inhibit microtubule polymerization, e.g., colchicine, destabilize dendrites and, consequently, prevent particle attachment and capture (Swetman Andersen et al, 2006). For this reason, we tested whether colchicine would inhibit formation of bead-cell complexes.…”
Section: Resultsmentioning
confidence: 99%
“…After coating the nanoparticle surface with these recombinant proteins, we showed that RGDS-PLA nanoparticles were more efficiently taken up by cells harboring α5β1 integrin receptors on their cell surface than uncoated or mutated KGES-coated nanoparticles. As a first approach, a subcutaneous vaccine model was developed to take advantage of the presence of dendritic cells presenting α5β1 integrin receptors on their surface in skin and to a less-extent in subcutaneous tissues, and their potential to migrate to peripheral draining lymph nodes [2122]. Mice were injected with different types of nanoparticles, coated with p24, an HIV antigen, and with or without RGDS- or KGES-FNIII9/10 recombinant proteins, and the antigenic potential of these formulations was estimated.…”
Section: Introductionmentioning
confidence: 99%